Inside Cover: Towards Shape Control of Metal Oxide Nanocrystals in Confined Molten Media (ChemNanoMat 1/2015). Issue 1 (May 2015) - Chen, Dennis P.; Fu, Jie; Skrabalak, Sara E.
Abstract : Shape‐Controlled Synthesis . In their Focus Review on10.1002/cnma.201500032 ((page 18, )) which is featured on the Inside Cover, Sara Skrabalak and co‐workers discuss the design principles involved in aerosol‐assisted molten salt syntheses of compositionally complex metal oxide nanomaterials. This technique can generate high‐quality nanocrystals by spatially and temporally confining their growth within droplets.